The effect of the fibres length on flexural strength and compressive strength of reinforced foamed concrete - Mohammed A.A. (American Institute of Physics Inc., 2024)
This experiment was carried out to determine the impact of fiber length on the mechanical properties of fiber-reinforced foamed concrete. The flexural strength was evaluated on almost 54 beam specimens with dimensions of 40 mm x 40 mm x 160 mm, as well as the compressive strength of 162 cubic specimens using two separate testing standards. Two different types of fiber were used to prepare specimens (fiberglass, steel fiber). Three fiber lengths (25 mm, 50 mm, 75 mm) were used, fiber to cement ratio was 4%, water curing conditions were adopted in this experiment. All the specimens were tested using the targeted dry density of (1160-1180 kg/m3). The different types of fiber increased the flexural capacity of the beams, but the specimens reinforced with (25 mm fiberglass) gave the highest flexural strength (2.1 Mpa). The compressive strength also had increased during different curing days, while using steel fiber (50 mm) gave the highest compressive strength (10.95 Mpa). However, 4% of (25mm) fiberglass is the optimum volume that should be included to contribute to the maximal flexural strength of foamed concrete. In addition, 4% of 50 mm steel fiber is an optimum volume that should be included to contribute to the maximal compressive strength. 2023 Author(s).